EFFECT OF PRE-TREATMENT AND AIR TEMPERATURE ON DRYING TIME OF CHERRY TOMATO - Doymaz, I.; Kipcak, A. S. (YILDIZ TECHNICAL UNIV, 2018)
The effects of pre-treatment and air temperature with on drying and rehydration characteristics of cherry tomato slices were studied. Drying experiments are carried out with the air temperature of 55, 65, and 75 degrees C. Drying time decreased with pre-treatment, and it also decreased considerably with increase in air temperature. The results indicated that the cherry tomatoes which were pre-treated with potassium solution were explored within the shortest time. Furthermore, superior rehydration was observed the samples which were pre-treated with potassium solution. The moisture effective diffusivity calculated from the second Fick's law of diffusion ranged from 2.26 to 6.22x10(-9) m(2)/s over the temperature range studied. Activation energy was estimated by an Arrhenius type equation and the activation energy values varied from 26.51 to 32.79 kJ/mol.
Keywords: Cherry tomato; Pre-treatment; Drying; Rehydration; effective moisture diffusivity; activation energy; MOISTURE DIFFUSIVITY; SLICES; KINETICS; MICROWAVE; MICROSTRUCTURE; BEHAVIOR; SORPTION; QUALITY; CARROT; COLOR; Thermodynamics